Bilateral robotic sympathectomy for recurrent ventricular tachycardia in a patient with complex cardiovascular history - John J Tumminello; Alexander Pohlman; Zaid M Abdelsattar; Julia M Coughlin (Journal of Surgical Case Reports, 2026)
Abstract A 76-year-old female with complex cardiovascular history requiring multiple open and transcatheter interventions presented with recurrent ventricular tachycardia (VT) and multiple implantable cardioverter-defibrillator (ICD) shocks. Her VT persisted despite maximal medical therapy. She underwent two left stellate ganglion blocks, which provided temporary VT suppression. She was found to have significant cardiomegaly and a large chronic descending aortic dissection on pre-operative workup, which did not require acute intervention. Given her persistent symptoms, she underwent bilateral robotic sympathectomy. She tolerated the procedure without complication and remained without ICD shocks at her 6-month clinic visit.